Comprehensive Performance Measurement System (CPMS) and Satisfaction of Malaysian Football Players: A Mediating Role of Reward - Zid, Azlina; Amiruddin, Rozita; Auzair, Sofiah Md; Janor, Hawati; Latif, Rozita Abdul; Asari, Fadli Fizari Abu Hassan; Hamid, Siti Fadhilah Abdul; Rajli, Mohammad Adzly (The journal of contemporary issues in business and government, 2021)
This paper aims to examine the relationship between Comprehensive Performance Measurement (CPMS) and football player satisfaction mediated by the role of reward. Structural Equation Model (SEM) through the PLS Smart Modeling verifies the construct and tests the hypothesis. There were 330 professional football players from the Super League and Malaysia Premier League involved in this study. The study findings showedthe reward acts as a social factor of an extrinsic motivator was fully internalised towards intrinsic motivation has a positive and significant impact on the relationship between CPMS and the football players’ satisfaction. It is based on the self-determination theory, comprising three basic psychological needs: autonomy, relatedness, and competence that can influence players’ satisfaction and enhance performance. This study was conducted in a football sports setting that adds to the knowledge of CPMS in performance evaluation based on self-determination theory. The CPMS, as a source of reference, can use to improve documentation from the aspects of setting skills standard, physical fitness, regulations, and strategies. It can increase the quality and performance of the players as well as the football team in Malaysia, all at once giving high levels of satisfaction